Spatial Rearrangement Using Pairwise Exchange Method (Case Study of PT. LMN) - Muhammad Bayu Aji Saputra; Boy Isma Putra (Universitas Muhammadiyah Sidoarjo, 2021)
PT. LMN is a company engaged in the manufacturing and outer production industry, the purpose of this research is to obtain a new layout design that can minimize the distance to move goods and the minimum total cost that can minimize the distance to move goods and the minimum total costs so as to reduce production costs, and obtain The new layout is better than the previous layout. Data processing begins by determining the initial sequence as a planning basis, then performing pairwise exchanges based on the initial sequence so as to produce several alternatives, do this stage until you get the smallest results. Lastly compares the new smallest order with the starting sequence. From the calculation, the results obtained are the proposed sequence (5 - 6 - 8 - 3 - 2 - 7 - 4 - 1 - 9) with a total value of 3450.5 meters. This proposal resulted in a total distance difference of 980.5 meters and a cost of IDR 11,736,8167 / per production. So that companies can reduce distance and also costs in each production process.